A porous flocculent carbon material based on mixed wine lees and its preparation method and application

By mixing distiller's grains from different fermentation processes and preparing porous carbon materials, the problems of high cost and environmental pollution in the production process of supercapacitor materials are solved, and materials with high specific capacitance and stability are prepared.

CN115893406BActive Publication Date: 2025-01-21GUILIN UNIV OF ELECTRONIC TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211545888.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-05
Publication Date
2025-01-21
Estimated Expiration
2042-12-05

AI Technical Summary

Technical Problem

There are problems of high production costs and environmental pollution in the production process of existing supercapacitor materials, and the specific capacitance performance of porous carbon materials has not yet achieved the best results.

Method used

Distillers grains from different fermentation processes are mixed, and carbon materials with porous structures are prepared through steps such as low-temperature pre-carbonization and alkaline material calcination, which reduces the amount of alkali and improves the specific capacitance performance of the material.

Benefits of technology

It is possible to reduce the alkali-carbon ratio under the same performance conditions, reduce environmental pollution and production costs, and at the same time improve the specific capacitance performance and stability of porous carbon materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115893406B_ABST
    Figure CN115893406B_ABST
Patent Text Reader

Abstract

The present invention discloses a porous flocculent carbon material based on mixed vinasse, which uses vinasse from solid fermentation and vinasse from semi-solid fermentation as raw materials, forms a carbon precursor through low-temperature pre-carbonization, and then directly mixes and calcines the carbon precursor and an alkaline substance to obtain a porous carbon material based on mixed vinasse. The obtained material is porous flocculent and has a specific surface area in the range of 1000-4000 m 2 g ‑1 . The lees used as raw materials must be a mixture of solid-state fermented lees and semi-solid-state fermented lees. The solid-state fermented lees are sweet potato lees or glutinous rice lees, and the semi-solid-state fermented lees are rice lees or sorghum lees. The preparation method comprises the following steps: 1. Preparation of carbon precursor; 2. Preparation of porous carbon material based on mixed lees. As a supercapacitor electrode material, when the current density is 1 A g ‑1 The specific capacitance ranges from 180 to 490 F g ‑1 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of supercapacitors, and in particular to a porous flocculent carbon material based on mixed wine lees, and a preparation method and application thereof. Background Art

[0002] As a new type of electrochemical energy conversion and energy storage device, supercapacitors have the characteristics of high power density, long cycle life, and wide operating temperature range. In addition to the specific capacitance performance, the main problems limiting their large-scale application are also limited by production costs and environmental pollution. Specifically, although capacitors based on high molecular conductive polymers have higher specific capacitance, their raw materials and products are toxic and polluting. In addition, the polymerization process, represented by ice baths, strong hydrochloric acid, and strong oxidant perchloric acid, has obvious environmental unfriendly problems.

[0003] The above problems can be effectively solved by using biomass as raw material to prepare porous carbon materials. Biomass raw materials have the following advantages: 1. Wide sources, low prices, and environmental friendliness; 2. Rich in elements, forming impurity elements in porous carbon materials, improving the wettability of the material surface, and thus improving the pseudocapacitance effect. Studies have shown that the specific surface area of ​​porous carbon materials has a significant effect on the specific capacitance performance. However, a large amount of experimental data shows that the larger the specific surface area, the better the specific capacitance performance. The reason is that the specific capacitance performance is also determined by the pore structure of the porous carbon material.

[0004] For example, in the prior art 1 (A Novel Porous N-and S-Self-Doped Carbon Derived from Chinese Rice Wine Lees as High-Performance Electrode Materials in a Supercapacitor. ACS Sustainable Chemistry & Engineering 2019), Tang et al. directly used glutinous rice as raw material and prepared bio-derived multilayer graphene low-dimensional carbon materials by one-step carbonization, obtaining a specific capacitance of 0.5Ag. -1 Down to 289.9F g -1 The direct reason for the lower capacitance performance of this technical solution is that the porous carbon material obtained from glutinous rice (due to untreated) has a specific surface area of ​​only 1371.5m 2 g -1 If the microstructure of the porous carbon material is adjusted, the specific capacitance performance can still be improved. In addition, this technical solution also has the problem of high cost - glutinous rice, as a food crop, has a high economic value, and the market price exceeds 3 yuan / 500g.

[0005] The invention believes that the use of wine lees as biomass raw materials can effectively solve the above-mentioned problems of microscopic morphology and grain crops. The reason is that the gas production phenomenon in the fermentation process of winemaking can achieve the pore-forming effect. In addition, yeast bacteria themselves have a specific morphology (cell structure) and a shell-core structure that can be formed in the subsequent carbonization process. The above two factors can achieve the regulation of the microscopic morphology of porous carbon materials, thereby improving the specific capacitance performance; in addition, grain can create economic value in the winemaking process, and the market price of the wine lees produced is not more than 1 yuan / 500g, and the disposal method is relatively single, mainly feeding livestock, and the economic value is low.

[0006] In addition, the breeding industry represented by domestic pigs has obvious cyclical problems, which in turn affects the economic value of the lees produced by brewing companies. Taking Sanhua Liquor in Guilin, Guangxi as an example, Sanhua Liquor produces more than 1,500 tons per year and produces more than 2,000 tons of lees. When domestic pig farming is in a downward cycle, since brewing companies have extremely limited ways to deal with lees, they can only dispose of them as waste, which not only fails to generate economic value, but also causes environmental problems. From the perspective of industry-university-research linkage, the preparation of supercapacitors using lees as raw materials is an extremely effective and economically valuable technology.

[0007] For example, in prior art 2 ("Characterization and electrochemical applications of a carbon with high density of surface functional groups produced from beer grains. Journal of Solid State Electrochemistry 2008, 13(6), 887-893"), Zhang et al. used beer grains as raw materials and obtained carbon materials after one-step carbonization, with the highest specific capacitance reaching 120 F g -1 , the specific capacitance performance of the obtained material is lower than that of the prior art 1. After research, the inventors found that the direct reason for the low specific capacitance is that the obtained material does not have a porous structure, which in turn leads to a low specific surface area of ​​the carbon material. After in-depth research, it was found that the fundamental reason why the fermentation process did not form a porous structure was that the beer fermentation process was liquid fermentation, that is, in the first slag and liquid separation process, the yeast mainly existed in the liquid and separated from the lees, resulting in most of the lees not undergoing a complete fermentation process, that is, no sufficient porous structure was formed in the subsequent fermentation process, resulting in lower material performance. In addition, the carbon-alkali ratio of the preferred embodiment of the prior art 2 is carbon: alkali = 1:4, which leads to excessive use of alkali, resulting in greater environmental pollution and production costs.

[0008] In order to solve the above problems, the lees with different fermentation processes can be used to obtain carbon materials with porous structures. After field research, it is known that the brewing process of Sanhua Liquor, a local specialty product of Guilin, Guangxi, is as follows: rice is used as raw material, and after adding yeast and koji, it is brewed by a semi-solid and semi-liquid fermentation process. Unlike the aforementioned beer fermentation process, rice participates in a complete fermentation in this fermentation process; and, in addition to producing carbon dioxide gas to form a unique circular porous structure, the most important thing is that this process is a semi-solid and semi-liquid fermentation throughout the process, without separating slag and liquid in the middle, which further promotes the formation of porous structures. These porous channels can better expose the various elements rich in themselves. On the basis of this porous structure, a rich and developed pore structure is obtained after a simple one-step activation treatment. These pore structures are conducive to the wettability of the material surface and the migration of charged particles. In addition, the heteroatoms rich in themselves can improve the pseudocapacitance effect, which is conducive to the storage of more charged particles, thereby effectively improving the performance of the material. The present invention shows that, as expected, a new porous carbon material with high energy storage performance is obtained.

[0009] As in prior art 3 (CN111017925A. Preparation and application of a novel porous carbon material with high energy storage performance), the inventor of the present invention used single Sanhua wine lees as raw material, and obtained a honeycomb-shaped material with a specific surface area ranging from 1000 to 4000 m after calcination and activation. 2 g -1 , the specific capacitance range is 350-500F g -1 The porous carbon material. After in-depth research by the inventors, the technical solution still has room for improvement. The reason is that the single Sanhua wine lees only undergoes one fermentation process, which directly leads to a single pore structure, thereby affecting the specific capacitance performance. Similarly, the carbon-alkali ratio of the preferred embodiment of technology 3 is carbon: alkali = 1:4, which leads to excessive use of alkali, resulting in greater environmental pollution and production costs.

[0010] In order to solve the above problems, the inventors adopted secondary fermentation technology in prior art 4 (CN113479879A. An activated carbon material based on secondary fermentation lees and its preparation method and application), and adjusted the pore structure of the lees raw material, and further improved the specific capacitance performance to 350-530F / g. However, when the carbon material prepared by this technology is used in supercapacitors, after 10,000 cycles of cycle testing, the specific capacitance retention rate is 92%, and its stability needs to be improved. In addition, due to the use of secondary fermentation, this technical solution will inevitably have the problem of a long time. At the same time, the preferred embodiment of technology 4 has a carbon-alkali ratio of carbon: alkali = 1:4, which still does not solve the problem of excessive alkali usage, resulting in greater environmental pollution and production costs.

[0011] The main drawbacks of alkali-activated activated carbon materials in supercapacitor applications are the large pollution in the production process and the low retention rate of specific capacitance of the obtained activated carbon materials during charge and discharge. Therefore, reducing the amount of alkali and improving the retention rate of specific capacitance during long-term charge and discharge have long been important issues that have not been resolved. Summary of the invention

[0012] The purpose of the present invention is to provide a porous carbon material based on mixed wine lees, and a preparation method and application thereof. On the premise of achieving the initial specific capacitance performance, that is, the technical effect, different inventive concepts are adopted to adjust the pore structure of wine lees, thereby reducing its necessary technical feature - secondary fermentation, and the technical problem of fermentation waiting time caused by this technical feature; and reducing the amount of alkali used and improving the retention rate of specific capacitance in long-term charging and discharging.

[0013] The basic principle of the present invention is that wine lees from different fermentations may have different structures and characteristics. If wine lees produced by different raw materials and different fermentation processes are mixed, it is possible to improve the efficiency of alkali activation during the alkali activation process, thereby obtaining the technical effect of reducing the alkali-carbon ratio under the conditions of the same performance (or improved performance), thereby reducing environmental pollution and production costs.

[0014] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0015] A porous flocculent carbon material based on mixed wine lees, which uses wine lees from solid fermentation and wine lees from semi-solid fermentation as raw materials, forms a carbon precursor through low-temperature pre-carbonization, and then directly mixes and calcines the carbon precursor and alkaline substances to obtain a porous carbon material based on mixed wine lees. The obtained material is honeycomb-shaped and has a specific surface area ranging from 1000 to 4000m 2 g -1 ;

[0016] The vinasse used as raw material must be a mixture of vinasse obtained through solid-state fermentation and vinasse obtained through semi-solid-state fermentation;

[0017] The lees obtained through solid-state fermentation are sweet potato lees or glutinous rice lees, and the lees obtained through semi-solid-state fermentation are rice lees or sorghum lees.

[0018] A method for preparing a porous flocculent carbon material based on mixed wine lees comprises the following steps:

[0019] Step 1, preparation of a carbon precursor, the raw materials are solid-state fermented lees and semi-solid-state fermented lees, firstly drying the solid-state fermented lees and semi-solid-state fermented lees at a drying temperature respectively, then mixing and grinding to obtain a mixed lees powder, and finally, pre-carbonizing the mixed lees under certain conditions to obtain a carbon precursor;

[0020] In the step 1, the lees obtained through solid-state fermentation are sweet potato lees or glutinous rice lees, and the lees obtained through semi-solid-state fermentation are rice lees or sorghum lees;

[0021] In the step 1, the calcination conditions are: in a nitrogen atmosphere, a pre-carbonization temperature of 300-600° C., a pre-carbonization time of 0.5-4 h, and a heating rate of 5° C. / min;

[0022] Step 2, preparation of a porous carbon material based on mixed vinasse, grinding and mixing the carbon precursor obtained in step 1 and an alkaline substance in a certain mass ratio, and then calcining under certain conditions, and the obtained product is soaked in a 1M hydrochloric acid solution, washed with deionized water to neutrality and dried to obtain a porous flocculent carbon material based on mixed vinasse;

[0023] In the step 2, the mass ratio of the carbon precursor to the alkaline substance is 1.0:(1-3);

[0024] In the step 2, the alkaline substance is one of potassium hydroxide, sodium hydroxide, calcium hydroxide and alkaline inorganic salt; in the step 2, the calcination conditions are: in a nitrogen atmosphere, the calcination temperature is 600-900° C., and the calcination time is 0.5-3h.

[0025] Application of porous flocculent carbon material based on mixed wine lees as supercapacitor electrode material when the current density is 1A g -1 When the specific capacitance value ranges from 180 to 490 F g -1 .

[0026] The porous flocculent carbon material based on mixed wine lees obtained by the present invention was tested experimentally, and the results are as follows:

[0027] Through transmission electron microscopy experiments, the prepared porous flocculent carbon material has a large number of holes on its surface;

[0028] Electrochemical tests have shown that the prepared porous flocculent carbon material has excellent capacitance performance. -1 When the specific capacitance value ranges from 180 to 490 F g -1 ; and good stability. After 20,000 cycles of stability testing, its specific capacitance retention rate is 99.9%.

[0029] Therefore, compared with the prior art, the present invention has the following advantages:

[0030] 1) Compared with the existing technology of alkali activation of similar wine lees carbon materials, the present invention reduces the amount of alkali used by 25%, reduces the production cost, improves the utilization rate of alkali, and greatly reduces the pollution to the environment;

[0031] 2) The porous flocculent carbon material prepared by this method overcomes the disadvantages of the alkali-activated carbon materials currently used in commercial supercapacitors, which generally have poor long-term operating stability and low specific capacitance retention rate;

[0032] 3) The overall process of the present invention is simple, the activation temperature is low, it is clean and environmentally friendly, the alkali content is reduced to improve process safety, and it is easy to realize industrialization.

[0033] Therefore, the porous flocculent carbon material prepared by the present invention has great application potential in the field of electrode materials for batteries and supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a TEM morphology image of the activated wine lees-derived porous carbon material GD-A13-700 in Example 1;

[0035] Figure 2 The lees-derived porous carbon material GD-A13-700 prepared in Example 1 was subjected to a current density of 1 Ag. -1 The GCD curve below;

[0036] Figure 3 The lees-derived porous carbon material GD-A13-700 prepared in Example 1 was subjected to a current density of 50Ag. -1 The following cycle test diagram;

[0037] Figure 4 The lees-derived porous carbon material GN-A13-700 prepared in Comparative Example 1 was subjected to a current density of 1 Ag. -1 The GCD curve below;

[0038] Figure 5 The lees-derived porous carbon material DG-A13-700 prepared in Comparative Example 1 was subjected to a current density of 1 Ag. -1 The GCD curve below;

[0039] Figure 6 The lees-derived porous carbon material G-A13-700 prepared in reference example 1 was subjected to a current density of 1Ag. -1 The GCD curve below;

[0040] Figure 7 The lees-derived porous carbon material D-A13-700 prepared in Reference Example 2 was subjected to a current density of 1Ag. -1 The GCD curve below. DETAILED DESCRIPTION

[0041] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0042] Example 1

[0043] A method for preparing a porous flocculent carbon material based on mixed wine lees comprises the following steps:

[0044] Step 1, preparation of a carbon precursor, the raw materials are sweet potato lees fermented by solid state fermentation and rice lees fermented by semi-solid state fermentation, firstly, the sweet potato lees and rice lees are dried at a drying temperature of 80°C, then, the sweet potato lees and rice lees are mixed and ground to obtain a mixed lees powder, and finally, the mixed lees are pre-carbonized under a nitrogen atmosphere at a calcination temperature of 500°C, a calcination time of 2h, and a heating rate of 5°C / min to obtain a carbon precursor, named GD-500;

[0045] Step 2, preparation of porous carbon material based on mixed wine lees, at a mass ratio of 1.0:3.0, 2g of the carbon precursor obtained in step 1 and 6g of potassium hydroxide were ground and mixed evenly, and then calcined under a nitrogen atmosphere at a calcination temperature of 700°C and a calcination time of 2h. The obtained product was soaked in 1M hydrochloric acid solution, washed with deionized water to neutrality and dried to obtain a porous flocculent carbon material based on mixed wine lees, named GD-A13-700.

[0046] In order to study the pore structure of GD-A13-700, TEM test was carried out. The test results are as follows Figure 1 As shown, GD-A13-700 has a fluffy floc-like structure with abundant macropores, mesopores and micropores.

[0047] In order to prove that GD-A13-700 can be used as a supercapacitor electrode material, a constant current charge and discharge test was performed. The test results are as follows Figure 2 As shown in Table 2, when the current density is 1A -1 When the specific capacitance reaches 481F g -1 .

[0048] In order to prove that GD-A13-700 has good rate performance, the charge and discharge test under current density was carried out. The test results are shown in Table 1. -1 When the specific capacitance is still as high as 380F g -1 . Shows good rate performance.

[0049] Table 1 Comparison of specific capacitance of GD-A13-700

[0050] Sample name <![CDATA[0.5Ag -1 ]]> <![CDATA[1Ag -1 ]]> <![CDATA[2Ag -1 ]]> <![CDATA[4Ag -1 ]]> <![CDATA[6Ag -1 ]]> <![CDATA[10Ag -1 ]]> GD-A13-700 <![CDATA[518F g -1 ]]> <![CDATA[481F g -1 ]]> <![CDATA[457F g -1 ]]> <![CDATA[429F g -1 ]]> <![CDATA[410F g -1 ]]> <![CDATA[380F g -1 ]]>

[0051] In order to prove that GD-A13-700 has good capacitance retention, in a three-electrode test system, the 6MKOH electrolyte was used in water at 50Ag -1The constant current charge and discharge test was carried out at a current density of . The test results are as follows Figure 3 As shown, after 20,000 cycles, when the specific capacitance retention rate was 99.9%, the coulombic efficiency was maintained at 98.7%, showing excellent capacitance retention rate.

[0052] In order to demonstrate the effect of mixed lees on electrochemical performance, comparative examples 1 and 2 are provided, wherein:

[0053] Comparative Example 1 is a porous carbon material prepared by using mixed lees of sweet potato lees and glutinous rice lees fermented by solid state fermentation as raw materials;

[0054] Comparative Example 2 is a porous carbon material prepared by using a mixture of semi-solid fermented rice grains and sorghum grains as raw materials;

[0055] For further comparison, reference examples 1 and 2 are provided, wherein:

[0056] Reference Example 1 is a porous carbon material prepared by using single lees of sweet potato lees fermented by solid state fermentation as raw material;

[0057] Reference Example 2 is a porous carbon material prepared by using single rice grains obtained through semi-solid fermentation as raw material.

[0058] Comparative Example 1

[0059] A porous carbon material based on sweet potato wine lees and glutinous rice wine lees. The steps not specifically described are the same as the preparation method described in Example 1, except that: the raw materials of step 1 are sweet potato wine lees and glutinous rice wine lees, the carbon precursor obtained in step 1 is named GN-500, and the porous carbon material obtained in step 2 is named GN-A13-700.

[0060] The constant current charge and discharge test results of GN-A13-700 are as follows Figure 5 As shown in Table 2, when the current density is 1A -1 When the specific capacitance reaches 300F g -1 .

[0061] Comparative Example 2

[0062] A porous carbon material based on rice wine grains and sorghum wine grains, wherein the steps not specifically described are the same as the preparation method described in Example 1, except that: the raw materials of step 1 are rice wine grains and sorghum wine grains, the carbon precursor obtained in step 1 is named DG-500, and the porous carbon material obtained in step 2 is named DG-A13-700.

[0063] The constant current charge and discharge test results of DG-A13-700 are as follows Figure 5 As shown in Table 2, when the current density is 1A -1When the specific capacitance reaches 201F g -1 .

[0064] Reference Example 1

[0065] A porous carbon material based on sweet potato lees, wherein the steps not specifically described are the same as the preparation method described in Example 1, except that: the raw material of step 1 is sweet potato lees, the carbon precursor obtained in step 1 is named G-500, and the porous carbon material obtained in step 2 is named G-A13-700.

[0066] The constant current charge and discharge test results of G-A13-700 are as follows Figure 5 As shown in Table 2, when the current density is 1A -1 When the specific capacitance reaches 288F g -1 .

[0067] Reference Example 2

[0068] A porous carbon material based on rice wine grains, wherein the steps not specifically described are the same as the preparation method described in Example 1, except that: the raw material of step 1 is rice wine grains, the carbon precursor obtained in step 1 is named D-500, and the porous carbon material obtained in step 2 is named D-A13-700.

[0069] The constant current charge and discharge test results of D-A13-700 are as follows Figure 5 As shown in Table 2, when the current density is 1A -1 When the specific capacitance reaches 189F g -1 .

[0070] Table 2 Summary of electrochemical data

[0071] Serial number Sample name <![CDATA[Specific capacitance (F g -1 )]]> Example 1 GD-A13-700 481 Comparative Example 1 GN-A13-700 300 Comparative Example 2 DG-A13-700 201 Reference Example 1 G-A13-700 288 Reference Example 2 D-A13-700 189

[0072] From the existing alkali activation technology of wine lees in the background technology, it can be known that the optimal carbon-alkali ratio is usually carbon: alkali = 1:4. When the proportion of alkali decreases, the specific capacitance of the corresponding material decreases rapidly. For example, in the prior art 3 in the background technology (CN111017925A. Preparation and application of a new type of porous carbon material with high energy storage performance), the specific capacitance can be as high as 463Fg when the carbon-alkali ratio is 1:4. -1 Once the carbon-base ratio drops to 1:3, its specific capacitance can quickly drop to 189 F g -1 How to change the process so that the electrode material can maintain a high specific capacitance while reducing the alkali ratio has become a key issue in the commercialization of alkali-activated carbon materials. However, it has not been solved. The present invention overcomes this problem by changing the lees material and achieves that when the alkali-carbon ratio is reduced to 1:3, the specific capacitance of the preferred embodiment 1 can be as high as 481F g -1 .

[0073] By comparing the experimental results of the above comparative example and reference example, the following conclusions can be analyzed and obtained:

[0074] 1. Comparison of Comparative Example 1 and Reference Example 1 shows that both fermentation methods of distiller's grains are solid-state fermentation. The raw materials of Comparative Example 1 are sweet potato distiller's grains and glutinous rice distiller's grains. When the current density is 1A g -1 When the specific capacitance of GN-A13-700 is 300Fg -1 The raw material of Reference Example 1 is single sweet potato lees. When the current density is 1A g -1 The specific capacitance of G-A13-700 is 288 F g -1 It can be seen that when the fermentation method of wine lees is solid-state fermentation, the specific capacitance of the porous carbon material obtained by mixing multiple wine lees or using a single wine lees as raw material is between 300 F g -1 The change is not obvious.

[0075] 2. Comparison of Comparative Example 2 and Reference Example 2 shows that the fermentation methods of the wine lees are both semi-solid fermentation. The raw materials of Comparative Example 2 are rice wine lees and sorghum wine lees. When the current density is 1A g -1 When the specific capacitance of DG-A13-700 is 201F g -1 The raw material of Reference Example 2 is a single rice lees. When the current density is 1A g -1 When the specific capacitance of D-A13-700 is 189F g -1 It can be seen that when the fermentation method of wine lees is solid-state fermentation, the specific capacitance of the porous carbon material obtained by mixing multiple wine lees or using a single wine lees as raw material is between 200 F g -1 The changes are not obvious.

[0076] 3. Comparison of Comparative Example 1 and Comparative Example 2 shows that even if the fermentation method is the same, the specific capacitance of the obtained carbon precursor is quite different. For example, when the current density is 1Ag -1 When the specific capacitance of GN-A13-700 obtained in Comparative Example 1 is 300F g -1 , while the specific capacitance value of DG-A13-700 obtained in comparative example 2 is 201F g -1 The alkali-to-carbon ratio used in the activation of the two is the same, which can be inferred that the activation effect (or pore-forming efficiency and utilization rate of the alkali) of the alkali activator in the two different fermentation types of wine lees is significantly different.

[0077] 4. Comparing Example 1 with the comparative example, it can be seen that the specific capacitance value of GD-A13-700 obtained in Example 1 is as high as 481F g -1. The lees obtained by two different fermentation methods can be used as raw materials to significantly improve the activation effect of the activator, so that when the carbon-base ratio is 1:3, it can reach the effect of the carbon-base ratio of 1:4 in the prior art 3 (CN111017925A. Preparation and application of a new type of porous carbon material with high energy storage performance) and the prior art 4 (CN113479879A. An activated carbon material based on secondary fermentation lees and its preparation method and application). When producing the same amount of activated carbon, the alkali dosage is reduced by 25%, the utilization rate of the alkali is improved, and the pollution to the environment and the production cost are greatly reduced. In addition, the GD-A13-700 obtained in Example 1 has excellent stability. After 20,000 cycles of stability testing, its capacitance retention rate is 99.9%, which is much higher than the capacitance retention rate of 92% in the prior art 4 after 10,000 cycles.

Claims

1. A porous flocculent carbon material based on mixed wine lees, characterized in that: Solid-state fermented wine lees and semi-solid-state fermented wine lees are used as raw materials, low-temperature pre-carbonization is performed to form a carbon precursor, and then the carbon precursor and an alkaline substance are directly mixed and calcined to obtain a porous flocculent carbon material based on mixed wine lees; The mass ratio of the carbon precursor to the alkaline substance is 1:3; The lees obtained through solid-state fermentation are sweet potato lees, and the lees obtained through semi-solid-state fermentation are rice lees.

2. A method for preparing a porous flocculent carbon material based on mixed wine lees, characterized in that The following steps are involved: Step 1, preparation of carbon precursor, the raw materials are solid-state fermented lees and semi-solid-state fermented lees, firstly drying the solid-state fermented lees and semi-solid-state fermented lees at 80-110° C. respectively, then mixing and grinding to obtain mixed lees powder, and finally, pre-carbonizing the mixed lees under certain conditions to obtain a carbon precursor; In the step 1, the calcination conditions are: in a nitrogen atmosphere, a pre-carbonization temperature of 400-600° C., a pre-carbonization time of 0.5-3 h, and a heating rate of 5° C. / min; In the step 1, the vinasse obtained by solid-state fermentation is sweet potato vinasse, and the vinasse obtained by semi-solid-state fermentation is rice vinasse; Step 2, preparation of a porous carbon material based on mixed vinasse, grinding and mixing the carbon precursor obtained in step 1 and an alkaline substance in a certain mass ratio, and then calcining under certain conditions, soaking the obtained product in a 1M hydrochloric acid solution, washing with deionized water to neutrality and drying, to obtain a porous carbon material based on mixed vinasse; In the step 2, the mass ratio of the carbon precursor to the alkaline substance is 1:3; In the step 2, the calcination conditions are: in a nitrogen atmosphere, the calcination temperature is 600-900° C., and the calcination time is 0.5-3 h.

3. The preparation method according to claim 2, characterized in that: In step 2, the alkaline substance is one of potassium hydroxide, sodium hydroxide, calcium hydroxide and alkaline inorganic salt.

4. The use of the porous flocculent carbon material based on mixed wine lees obtained by the preparation method according to claim 2 as a supercapacitor electrode material, characterized in that: When the current density is 1A -1 When the specific capacitance value ranges from 180 to 490 F g -1 .

Citation Information

Patent Citations

  • Activated carbon material based on secondarily fermented vinasse as well as preparation method and application of activated carbon material

    CN113479879A

  • Method for preparing biochar by using Chinese spirit vinasse and recycling intermediate wastes

    CN108213050A

  • Preparation and applications of novel porous carbon material with high energy storage performance

    CN111017925A